2015
DOI: 10.1016/j.theriogenology.2015.04.025
|View full text |Cite
|
Sign up to set email alerts
|

Embryo vitrification in rabbits: Consequences for progeny growth

Abstract: The objective of this research is to examine if there are any effects of the rederivation procedures on rabbit growth pattern and on weight of different organ in adults. For this purpose, three experiments were conducted on two different groups of animals (control group and vitrified-transferred group) to evaluate the possible effect of embryo manipulation (vitrification and transfer procedures) on future growth traits. The first experiment studies body weight from 1 to 9 weeks of age from the two groups. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 45 publications
3
11
1
Order By: Relevance
“…Finally, in the third generation, the heritable epigenetic effects generated by the rederived technique could emerge and become present. Lavara et al [23] demonstrated that vitrification and transfer procedures involved in a rederivation programme for rabbit embryos have long-term consequences on rabbit growth patterns and might affect some growth-related traits in rabbits. Therefore, if the genetic artefacts introduced by the rederivation process were similar in both generations, evaluating their phenotypic differences from the third generation post-rederivation should be the most appropriate method with a minor cumulative genetic drift variance [47].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, in the third generation, the heritable epigenetic effects generated by the rederived technique could emerge and become present. Lavara et al [23] demonstrated that vitrification and transfer procedures involved in a rederivation programme for rabbit embryos have long-term consequences on rabbit growth patterns and might affect some growth-related traits in rabbits. Therefore, if the genetic artefacts introduced by the rederivation process were similar in both generations, evaluating their phenotypic differences from the third generation post-rederivation should be the most appropriate method with a minor cumulative genetic drift variance [47].…”
Section: Discussionmentioning
confidence: 99%
“…In the case of organ weights, data were corrected using body weight as a covariate. The growth rate was estimated by nonlinear regression using the Gompertz curve equation, well suited for rabbits [ 15 , 30 ]: y = a exp(−b exp(−kt)), where y is the observed body weight of one individual at a specific age (t). The rest of the parameters (a, b and k) of the Gompertz function have a biological interpretation, k being the parameter related to the rate of maturing (growth rate).…”
Section: Methodsmentioning
confidence: 99%
“…Recently, different vitrification methods for cryopreservation of COCs have been reported in yaks (Pan, Cui, He, et al., ), pigs (Uchikura, Matsunari, Nakano, Hatae, & Nagashima, ), sheep (Hosseini et al., ), rabbits (Lavara, Baselga, Marco‐Jimnez, & Vicente, ) and mice (Mazur & Paredes, ). Vitrification methods include the cryoloop (Lane, Schoolcraft, Gardner, & Phil, ), solid surface (Dinnys, Dai, Jiang, & Yang, ) and CT methods (Kuwayama, ).…”
Section: Discussionmentioning
confidence: 99%